The Effect of Using Video Tutorial to The Student’s Ability in Writing Procedure Text of Grade Seventh at SMP Negeri 2 Siantar - cryday yanti gea, Ephy; Napitupulu, Selviana; Melisa P Hutabarat, Novra (The Future of Education Journal, 2024)
This study aims to determine the effect of video tutorial media on students' ability to write procedure texts in Class VII SMP Negeri 2 Siantar. This research uses quantitative research methods with quasi-experimental design. The population of this study were the seventh grade students of SMP Negeri 2 Siantar in the school year 2024/2025. This study used purposive sampling to select the sample. The researchers took two classes as samples. The samples were class VII-1 as a control class of 30 students and class VII-5 as an experimental class of 30 students. The experimental class was taught using video tutorial media while the control class was taught using conventional methods. Data was collected by giving pre-test and post-test to both the classes. This research instrument is in the form of essay questions with a total of 1 question. The results showed that the average score of the experimental class was higher than the average score of the control class. The average score of the experimental class in the pre-test was 48.06 and the average score in the post-test was 77. While the average score of the control class in the pre-test was 50.7 and the average score in the post-test was 71.46. Then, after conducting a t-test, the researcher found that the t-count was higher than the t-table (2.91>1.672). Therefore, the alternative hypothesis (Ha) of this study was accepted and the null hypothesis (H0) was rejected. It can be concluded that the effect of video tutorial media is very significant on the procedural writing ability of seventh grade students of SMP Negeri 2 Siantar.